Integrated Management Practices for Canopy–Topsoil Improves the Grain Yield of Maize with High Planting Density - Xuefang Sun; Xuejie Li; Wen Jiang; Ming Zhao; Zhuohan Gao; Junzhu Ge; Qing Sun; Zaisong Ding; Baoyuan Zhou (Plants, 2023)
Inappropriate spatial distribution of canopy and roots limits further improvements to the grain yield of maize with increased planting density. We explored an integrated management practice called strip deep rotary with staggered planting (SRS) which includes comprehensive technology for both canopy layers and topsoil. Here, field experiments were conducted under two maize cropping systems (spring maize and summer maize) to evaluate the effect of SRS on the spatial distribution of the canopy and roots for maize under high planting density (90,000 plants ha−1) and to determine the physiological factors involved in yield formation. Compared with conventional management practices (no-tillage with single planting, NTS), SRS decreased the LAI of the middle to top layers while improving the light distribution of the middle and lower layers by 72.99% and 84.78%, respectively. Meanwhile, SRS increased the root dry weight density and root sap bleeding by 51.26% and 21.77%, respectively, due to the reduction in soil bulk density by an average of 5.08% in the 0–40 cm soil layer. SRS improved the SPAD in the ear and lower leaves and maximized the LAD, which was conducive to dry matter accumulation (DMA), increasing it by 14.02–24.16% compared to that of NTS. As a result, SRS increased maize grain yield by 6.71–25.44%. These results suggest that strip deep rotary combined with staggered planting noticeably optimized the distribution of light in the canopy and reduced the soil bulk density to promote root vitality and growth, to maintain canopy longevity, and to promote the accumulation of dry matter, which eventually increased the grain yield of the maize under high planting density conditions. Therefore, SRS can be considered a better choice for the sustainable high yield of maize under high-density planting conditions in the NCP and similar areas throughout the world.